Transcriptomic Profiling of Arabidopsis thaliana Mutant pad2.1 in Response to Combined Cold and Osmotic Stress - Kumar, Deepak (PLoS One, 2015)
The contribution of glutathione (GSH) in stress tolerance, defense response and antioxidant signaling is an established fact. In this study transcriptome analysis of pad2.1, an Arabidopsis thaliana mutant, after combined osmotic and cold stress treatment has been performed to explore the intricate position of GSH in the stress and defense signaling network in planta. Microarray data revealed the differential regulation of about 1674 genes in pad2.1 amongst which 973 and 701 were significantly up- and down-regulated respectively. Gene enrichment, functional pathway analysis by DAVID and MapMan analysis identified various stress and defense related genes viz. members of heat shock protein family, peptidyl prolyl isomerase (PPIase), thioredoxin peroxidase (TPX2), glutathione-S-transferase (GST), NBS-LRR type resistance protein etc. as down-regulated. The expression pattern of the above mentioned stress and defense related genes and APETALA were also validated by comparative proteomic analysis of combined stress treated Col-0 and pad2.1. Functional annotation noted down-regulation of UDP-glycosyl transferase, 4-coumarate CoA ligase 8, cinnamyl alcohol dehydrogenase 4 (CAD4), ACC synthase and ACC oxidase which are the important enzymes of phenylpropanoid, lignin and ethylene (ET) biosynthetic pathway respectively. Since the only difference between Col-0 (Wild type) and pad2.1 is the content of GSH, so, this study suggested that in addition to its association with specific stress responsive genes and proteins, GSH provides tolerance to plants by its involvement with phenylpropanoid, lignin and ET biosynthesis under stress conditions.